2021
DOI: 10.1155/2021/2603641
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin Treatment for Parkinson’s Disease Psychosis in Clinical Practice

Abstract: Background. Parkinson’s disease psychosis (PDP) is a common, nonmotor symptom of Parkinson’s disease (PD), which may affect up to 60% of patients and is associated with impaired quality of life, increased healthcare costs, and nursing home placement, among other adverse outcomes. Characteristic symptoms of PDP include illusions; visual, auditory, tactile, and olfactory hallucinations; and delusions. PDP symptoms typically progress over its course from being mild, infrequent, and often untroubling to complex, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Pimavanserin, a newer atypical antipsychotic similar to clozapine, and without evidence for worsening of motor symptoms in PD, has been suggested as a plausible safer alternative treatment [9]. Pimavanserin acts as an inverse agonist and antagonist at serotonin 5-HT2A receptors with high binding affinity and at serotonin 5-HT2C receptors with lower binding affinity.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pimavanserin, a newer atypical antipsychotic similar to clozapine, and without evidence for worsening of motor symptoms in PD, has been suggested as a plausible safer alternative treatment [9]. Pimavanserin acts as an inverse agonist and antagonist at serotonin 5-HT2A receptors with high binding affinity and at serotonin 5-HT2C receptors with lower binding affinity.…”
Section: Treatmentmentioning
confidence: 99%
“…Behavioral and neuropsychiatric symptoms including apathy, depression and notably psychosis might be a key feature of dementia in PD/DLB and they often have a greater impact than cognitive problems [7]. Symptomatic treatments have been applied for LBDrelated dementia and the concurrent neuropsychiatric problems while quest for novel etiological therapies is ongoing [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Dashtipour et al reported a case series of PMV treatment for PD psychosis with clinical tips. Table 4 was adapted from the study of Dashtipour et al [ 65 ]. It is worth mentioning that US prescribers of PMV must provide medical documentation of psychosis and the reason for its indication, which can sometimes affect the use of PMV for behavioral management [ 66 ].…”
Section: Pimavanserin Clinical Experiencementioning
confidence: 99%
“…The therapeutic responsiveness of pimavanserin may be enhanced or facilitated by other PD-related drugs or interventions, such as cholinesterase inhibitors and deep brain stimulation[ 98 ]. Currently, there is limited understanding of the discrepancy between pimavanserin and other antipsychotics with respect to efficacy, safety, and tolerability and further large-scale multicenter studies are required to confirm the clinical utility of pimavanserin in other clinical settings[ 84 ].…”
Section: Treatment and Managementmentioning
confidence: 99%